2019
DOI: 10.3168/jds.2018-15960
|View full text |Cite
|
Sign up to set email alerts
|

The effect of host genetics on in vitro performance of bovine monocyte-derived macrophages

Abstract: The dynamic interaction between the host and pathogens, along with environmental factors, influences the regulation of mammalian immune responses. Therefore, comprehensive in vivo immune-phenotyping during an active response to a pathogen can be complex and prone to confounding effects. Evaluating critical fundamental aspects of the immune system at a cellular level is an alternative approach to reduce this complexity. Therefore, the objective of the current study was to examine an in vitro model for functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 73 publications
(76 reference statements)
2
22
0
Order By: Relevance
“…This cellular phenotype was strongly associated with host genetics. The heritability of NO − production was 77%, similar to the heritability of NO − production by peritoneal macrophages in mice 21,28 . These findings showed that NO production could be considered as a genetic index to classify MDMs.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…This cellular phenotype was strongly associated with host genetics. The heritability of NO − production was 77%, similar to the heritability of NO − production by peritoneal macrophages in mice 21,28 . These findings showed that NO production could be considered as a genetic index to classify MDMs.…”
Section: Discussionsupporting
confidence: 59%
“…These two groups were exposed to the same bacteria with exactly similar MOI in a similar environment. The only difference between these two groups was their genetic architecture as we have previously shown 21 .…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations